The Influence of Business Performance on Credit Accessbility to Micro and Small Enterprises (MSEs) - Teti Chandrayanti (Yayasan Ilomata, 2022)
This study investigates the influence of performance of micro and small enterprises on accessing external finance from banks. This study used data from 30 respondents of MSEs by survey questionnaires in West Sumatera, Indonesia. The study used simple linear regression model with the access of credit as the dependent variable and performance of business as the independent variable. The results confirm that the performance of MSEs significantly affect accessibility to external finance from banks. The study recommended that both financial and non-financial measures are important in determining access to credit. Therefore, businesses have to improve their resources in order to increase their performance and to improve their accessibility to credit. Due to their limitations in preparing financial statements, the hybrid approach of using financial and non-financial measures should be considered by financial institutions to assess the conditions of the business. A conductive environment should be created for good relationships among stakeholders.